Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) Desa Lattimu Kecamatan Bola Kabupaten Wajo - Muhammad Jumsar; Jamal Qadar; Burhanuddin Burhanuddin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Accountability in managing Village Fund Allocation (ADD) is crucial to ensure effective, efficient, and compliant use of the funds. This study investigates how accountability in ADD management is implemented in Lattimu Village, Bola Subdistrict, Wajo Regency, through planning, implementation, and reporting stages while identifying supporting and inhibiting factors. Using a descriptive qualitative approach with a case study method, data were gathered through interviews, observations, and documentation. The findings reveal that ADD accountability in Lattimu Village aligns with applicable regulations, covering planning, implementation, and reporting processes. Active community participation during village meetings emerged as a significant supporting factor. However, challenges such as limited technological proficiency among village officials and the community's low educational levels hinder effective management. The study recommends increasing human resource capacity through technical training and fostering greater community involvement in decision-making forums. Strengthening these aspects is expected to enhance the transparency, effectiveness, and efficiency of ADD management, ensuring better outcomes for the village development initiatives.